Osteopontin facilitates West Nile virus neuroinvasion via neutrophil “Trojan horse” transport - Paul, Amber M. (Sci Rep, 2017)
West Nile virus (WNV) can cause severe human neurological diseases including encephalitis and meningitis. The mechanisms by which WNV enters the central nervous system (CNS) and host-factors that are involved in WNV neuroinvasion are not completely understood. The proinflammatory chemokine osteopontin (OPN) is induced in multiple neuroinflammatory diseases and is responsible for leukocyte recruitment to sites of its expression. In this study, we found that WNV infection induced OPN expression in both human and mouse cells. Interestingly, WNV-infected OPN deficient (Opn (−/−)) mice exhibited a higher survival rate (70%) than wild type (WT) control mice (30%), suggesting OPN plays a deleterious role in WNV infection. Despite comparable levels of viral load in circulating blood cells and peripheral organs in the two groups, WNV-infected polymorphonuclear neutrophil (PMN) infiltration and viral burden in brain of Opn (−/−) mice were significantly lower than in WT mice. Importantly, intracerebral administration of recombinant OPN into the brains of Opn (−/−) mice resulted in increased WNV-infected PMN infiltration and viral burden in the brain, which was coupled to increased mortality. The overall results suggest that OPN facilitates WNV neuroinvasion by recruiting WNV-infected PMNs into the brain.